Community-Based Health Insurance in Rwanda - Pathé Diop, Francois; Butera, Jean Damascene (World Bank, Washington, DC, 2012)
Rwanda has lived one of the most tragic moments of its history with the genocide of 1994, which resulted in nearly one million deaths, and the destruction of the social fabric of the country. Mutual aid and community solidarity value systems have remained resilient traits of Rwanda's society, and continue to be translated in coping strategies in the health care area. After the 1994 war, however, mutual aid initiatives have emerged in the health sector as community responses to the reintroduction of user-fees in public, and mission health facilities. Building on these community initiatives, health authorities, and non-government organizations have moved these emerging strategies to a deliberate strategy of building community-based health insurance schemes in the health sector. Community-based health insurance schemes (CBHI) provided also a platform for the compilation of information to support the assessment of CBHI schemes, and to familiarize health sector actors, and partners with the strategies needed to support their implementation on a large scale. CBHI schemes in Rwanda are health insurance organizations based on a partnership between the community and health care providers. As consensus built-up on the benefits of the CBHI schemes, a multi-level leadership developed in the country to provide support to the adaptation, and extension of the schemes. Political leaders at the central level, starting from the Presidency, called for the mobilization of all actors to support the implementation of CBHI schemes throughout the country.